Assessing the management of patients with type 2 diabetes in Bangladesh during pre- and post-COVID-19 era and the implications: A pilot study - Farhana Akter, Mainul Haque, Sanira Akter, Gias Uddin, Naim Chy, Francis Kalemeera, Amanj Kurdi, Kona Chowdhury, Brian Godman (Journal of Applied Pharmaceutical Science, 2022)
There is growing concern with the management of patients with type 2 diabetes (T2DM) across countries with suboptimal management increasing morbidity, mortality, and costs. In Bangladesh, the number of patients with diabetes will increase to an estimated 13.7 million by 2045, mainly T2DM, unless addressed. Alongside this, continued concerns with high rates of uncontrolled blood glucose levels as well as complication rates, including both microvascular and macrovascular complications in patients with T2DM in Bangladesh. This adds to the cost of care, which can be a concern among patients in Bangladesh with high co-payment rates. Alongside this, concerns with the impact of COVID-19 and associated lockdown measures on the care of these patients. Greater proactivity in managing these patients can help. Consequently, a need to ascertain what data is routinely collected in public hospitals in Bangladesh, including during the pandemic, to guide care. A pilot study was undertaken among eight patients in Chittagong Medical College using purposely designed case report forms to ascertain the extent of clinical information collected and their care against agreed target levels. There was typically poor control of blood glucose levels among the eight patients, which has resulted in increased prescribing of insulin. However, better control of blood pressure, lipids and albumin levels. There were appreciable missing knowledge gaps, especially during the pandemic. This needs addressing.
Keywords: Bangladesh, complications, diabetes, guidelines, health policies, type 2 diabetes